Optimization of Inclusive Education Through the Implementation of Artificial Intelligence: Opportunities and Challenges - Jamaludin, Haris; Hartono, Budi; Kuncoro, Arsito Ari (University of Science and Computer Technology, 2025)
Inclusive education is critical to ensuring equitable learning opportunities for all students, regardless of their abilities or backgrounds. This study aims to analyze the optimization of inclusive education by implementing artificial intelligence (AI), focusing on identifying the opportunities and challenges that arise. A systematic literature review was conducted as the research method, referencing five journals related to the application of AI in education and other relevant sectors. The findings reveal that AI has significant potential to enhance the quality of inclusive education by enabling personalized learning materials, real-time student data analysis, and improved teacher-student interactions. These advancements can help address diverse learning needs and promote a more inclusive learning environment. However, several challenges must be addressed, including technological disparities, limited infrastructure, and ethical concerns related to AI usage, such as data privacy and algorithmic bias. The study concludes that the successful implementation of AI in inclusive education requires collaborative efforts among governments, educational institutions, and other stakeholders to ensure accessibility, equity, and sustainability. Key recommendations include the development of supportive policies, enhancement of digital literacy among educators and students, and investment in technological infrastructure to bridge the digital divide. This research contributes to the growing discourse on the integration of AI in education, providing insights for policymakers and practitioners aiming to harness AI's potential for inclusive education.